2021
DOI: 10.1038/s41598-021-87248-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metabolic syndrome and its associated risk factors among staffs in a Malaysian public university

Abstract: Public health systems are concerned with the commensurate rise of metabolic syndrome (MetS) incidence across populations worldwide, due to its tendency to amplify greater risk of diabetes and cardiovascular diseases within communities. This study aimed to determine the prevalence of MetS and its associated risk factors among staffs in a Malaysian public university. A cross-sectional study was conducted among 538 staffs from the Universiti Kebangsaan Malaysia (UKM) between April and June 2019. MetS was defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 56 publications
4
29
1
1
Order By: Relevance
“…Younger age with CVD may have increase sick leave usage and affect the work quality and produtivity. In terms of gender, this study found that males were more likely to have hypertension and smoked tobacco The concurrent ndings had the same results with pprevious studies [17], [33]. Females had higher odds of getting hypercholesterolemia, obesity and being physically inactive, which may contribute to a higher risk of CVD at later age [34].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Younger age with CVD may have increase sick leave usage and affect the work quality and produtivity. In terms of gender, this study found that males were more likely to have hypertension and smoked tobacco The concurrent ndings had the same results with pprevious studies [17], [33]. Females had higher odds of getting hypercholesterolemia, obesity and being physically inactive, which may contribute to a higher risk of CVD at later age [34].…”
Section: Discussionsupporting
confidence: 76%
“…In terms of working sectors, the government & semi-government sector workers had higher odds of multiple CVD risks such as diabetes, hypertension, hypercholesterolemia, smoking and obesity as found in previous studies [17], [32], [43]. There are many possible reasons for this nding, such as older age and sedentary working.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In stage one, participants were required to complete a self-administered questionnaire that consisted of items on socio-demographic characteristics (e.g., gender, age) and health status. The description for this study can be found elsewhere [ 19 ]. In stage two, participants were asked to complete questions on quality of life, mindfulness, work engagement, family life satisfaction, subjective well-being, and lifestyle.…”
Section: Methodsmentioning
confidence: 99%
“…The moderate physical activity level was defined as 3 or more days of vigorous-intensity activity of at least 20 min/day, 5 or more days of moderate-intensity activity or walking for at least 30 min/day, or 5 or more days of any combination of walking, moderate-intensity, or vigorous-intensity activities to achieved a minimum of at least 600 MET-minutes/week. Respondents were classified as having a low physical activity level if they did not meet either of the two criteria above [31][32][33][34]. Health-related information, such as employees' comorbid conditions (diabetes, hypertension, or hypercholesterolemia), was based upon self-reported measures as diagnosed by a medical doctor, or if they were currently under treatment with antihypertensives, oral hypoglycemics, or lipid-lowering drugs.…”
Section: Study Instrumentmentioning
confidence: 99%